Auditoría en seguridad vial K 0 + 300 al K 6 + 300, de la ruta nacional 25 (Código 2507 tramo Cerritos-la Virginia). Municipio de Pereira, Risaralda (2021)
This degree project presents the audit in road safety (ASV) to the Vial section K 0 + 300 to K 6 + 300, of National Route 25 (Code 2507 section Cerritos-La Virginia) Municipality of Pereira, Risaralda, because there is no there is evidence from previous audits. The (ASV) was performed on the variables: signals, barriers and design consistency, having as working instruments formats for photographic records and speeds, specialized software for risk map analysis (Qgis Software), design consistency (Signals software). ), in the first phase, field work is carried out, which allows identifying infrastructure and security conditions, with which the road has, in the second phase the information is analyzed in software and finally the results are presented , the required signage and the installation of some that are missing, maintenance of others, there are physical risks such as: forceful elements on the road and safety barriers that do not exist and frequent evidence of aggressive behavior on the part of road actors.